Defects caused by degradation - A stumbling block for nanocomposites in thin film capacitors - Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W. (ICD 2022 - IEEE 2022 4th International Conference on Dielectrics, Proceedings, 2022)
The aim of this study is to shed light on why the often-praised beneficial effects of nanoparticles on dielectric breakdown strength are not observed in biaxially oriented PP-based films. Therefore, thin films of capacitor grade PP and nanocompounds containing one of two SiO2 based nanoparticles (pyrogenic and colloidal) at 2wt.% and 4wt.% were produced at a pilot scale thin film production line. Additionally, neat PP was deliberately degraded to a similar extent using cyclic extrusion on a twin-screw extruder. After cast film extrusion and biaxial stretching using a Karo IV lab stretcher, all films were tested for their dielectric strength, surface roughness, molar mass and particle dispersion using a diamond tip profilometer, HT-GPC and SEM. All films showed a reduction in molar mass of up to 50 % in mathrmM_mathrmw followed by a linear decrease in breakdown strength. It is known that the degradation mechanisms in PP lead to the inclusion of radicals, double bonds and carbonyl groups in the polymer chain, decreasing the width of the bandgap and thereby reducing dielectric strength in a stronger way than nanoparticles could enhance it. This study shows that the negative effect of degradation during processing is probably stronger than the superimposed and potentially beneficial effect of adding nanoparticles.
CRIS-Team Scopus Importer:2022-09-30